2007
DOI: 10.1007/bf03033999
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dynamic FDG-microPET study in a rabbit turpentine-induced inflammatory model and in a rabbit VX2 tumor model

Abstract: Our results suggest the possibility of shortening the overall testing time in clinical practice by adopting dual-time-point imaging rather than single-time-point imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…The preliminary data confirmed a possible role for 68 Ga-citrate in the diagnosis of bone infections [5]. These reports initiated various animal studies in infectious animals as well as reporting production routes [6][7][8][9] and also some groups demonstrated the application of the tracer in atherosclerotic plaques in animal models as inflammatory applications [10] and also some reports on inflammated rabbit models [11], yet not much data and studies have been reported for the evaluation of inflammation in animal models for determination imaging time as well as other factors.…”
Section: Introductionmentioning
confidence: 60%
“…The preliminary data confirmed a possible role for 68 Ga-citrate in the diagnosis of bone infections [5]. These reports initiated various animal studies in infectious animals as well as reporting production routes [6][7][8][9] and also some groups demonstrated the application of the tracer in atherosclerotic plaques in animal models as inflammatory applications [10] and also some reports on inflammated rabbit models [11], yet not much data and studies have been reported for the evaluation of inflammation in animal models for determination imaging time as well as other factors.…”
Section: Introductionmentioning
confidence: 60%
“…As liver inflammation may occur after ingestion of the toxin, tumor detectability in the TTA rat model might be diminished by the presence of TAA-induced centrilobular liver inflammation [36]. Due to different FDG uptake kinetics between inflammatory and tumoral foci, it might be useful to distinguish these two entities by scanning the subject at a later time period [37]. In our study, the use of an optimal scan time (90 minutes postinjection of the FDG) resulted in no FDG accumulation in cirrhotic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…This uptake trend was in accordance with the time window of macrophage infiltration into inflammatory foci. Because focal turpentine oil acted as constant stimuli which was difficult to be eliminated by inflammatory cells, inflammatory muscle would turn to chronic inflammation at day 3-6 post inflammation modeling 27. In acute inflammation phase which is 1-2 days after turpentine oil injection, lymphocytes and neutrophils are the major cell population within inflammatory foci.…”
Section: Discussionmentioning
confidence: 99%